2022
DOI: 10.3390/su14031246
|View full text |Cite
|
Sign up to set email alerts
|

Research on Art Teaching Practice Supported by Virtual Reality (VR) Technology in the Primary Schools

Abstract: Nowadays, teaching and learning methods are constantly changing with the development and popularization of information technology. Many teaching activities are exploring the integration of virtual technology. However, the specific effects of VR are challenging to verify. In this paper, “teaching in VR environment” and “traditional teaching” were designed to carry out a series of teaching comparison practices between two groups of a primary school. By analyzing the experimental data of the experimental group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…With the widespread use of information technology, teaching and learning techniques are continually evolving. Virtual technology is being used in a wide range of educational endeavors [20]. VR is an effective intervention method for this demographic, although further studies using current VR technology are needed.…”
Section: Overview Of Virtual Reality In the Course Of Later Stagementioning
confidence: 99%
“…With the widespread use of information technology, teaching and learning techniques are continually evolving. Virtual technology is being used in a wide range of educational endeavors [20]. VR is an effective intervention method for this demographic, although further studies using current VR technology are needed.…”
Section: Overview Of Virtual Reality In the Course Of Later Stagementioning
confidence: 99%
“…Persiapan yang tepat dengan memanfaatkan peran Teknologi Website menggunakan WebVR. WebVR adalah Website Virtual Reality yang membuat pengguna dapat berinteraksi melalui lingkungan yang ada dalam internet (dunia maya) yang telah di simulasikan oleh komputer, sehingga pengguna sedang merasakan berada dalam dunia virtual [4], [5], [6], [7], [8].…”
Section: Pendahuluanunclassified
“…In addition to making systems accessible and minimizing manufacturing costs by building scalable and scalable models easily and quickly (Hatta et al, 2022). Computer vision advances have enabled the blending of physical and digital worlds and 3D human, computer, and environment interactions (Hui et al, 2022) as shown in Figure1. It also uses augmented reality and virtual reality techniques to train students by building an interactive virtual reality for training that is safe without risk and at a lower cost, where the same experience can be repeated many times without the need to pay additional amounts (Kanade & Duffy, 2022).…”
Section: Introductionmentioning
confidence: 99%